Stretching hydrolysis in LiI-Li2WO4-Li3PO4 by infrared spectroscopy - A.H. Ahmad; M.Z.A. Yahya; R. Puteh; A.K. Arof (Indonesian Journal of Physics, 2004)
Infrared spectroscopy is a useful tool to probe the formation of polyhedral structures in alkali halide-oxysalts. LiI-Li2WO4- Li3PO4 is an example of alkali halide-oxysalt. These materials have been proposed as superionic materials for use as electrolytes in electrochemical devices. One of the pertinent problems in lithiated superionic materials is their hygroscopic property that can seriously affect the conductivity of the materials. In the present work, LiI-Li2WO4- Li3PO4 has been prepared by the sintering method in order to ensure removal of water from the samples. Fourier Transform Infrared (FTIR) spectra show that the band at 1634 cm-1 due to lithium tungstate, the band at 1628 cm-1 due to lithium iodide has overlapped to form a single band at around 1640 cm-1. The two bands at 1050 and 590 cm-1are assigned to pure lithium phosphate. The FTIR spectrum of the ternary system is almost similar to that of the binary system and they are quite similar to the spectrum of lithium tungstate. FTIR shows there is a strong broad band centered at 3400 cm-1 in the binary sample but the band decreases in width on addition of Li3PO4. This band is an indication of stretching hydrolysis. A medium band is also observed at 1505 cm-1, which is due to H-O-H bending motion This band almost disappears as the amount of Li3PO4 is increased to 30 wt.%. These results indicate that with further treatment the sample LiI-Li2WO4- Li3PO4 has potential for use in lithium batteries.